Race and Rationality Revisited: an Empirical Examination of Differential Travel Patterns to Acquire Drugs Across Geographic Contexts - Wagner, Jascha (American journal of criminal justice, 2023)
The journey to drug crime literature has found that, in cities, Black people travel shorter distances from their homes before being arrested relative to White people. Per race and rationality theory, the racialization of space shapes the decision-making processes of people arrested for drug offenses. Because residential segregation patterns and racialized social structures differ across levels of urbanization, this study uses negative binomial regression models to evaluate Black-White differences in journeys to crime for drug possessions, and the study assesses socioeconomic and opportunity characteristics of offense locations at the micro-level using drug arrest reports across the State of Delaware. We find that travel distances and predictors of offense locations differ across geographic areas (i.e., small cities, suburban areas, small towns, rural areas, and touristic rural areas). A place’s racial composition, concentrated disadvantage, and opportunity characteristics differently impact offense locations across geographic areas. Accordingly, in studying journeys to crime, researchers should consider the various ways that race shapes constructions of crime and place across the rural–urban continuum.